2020
DOI: 10.21451/1984-3143-ar2019-0083
|View full text |Cite
|
Sign up to set email alerts
|

Lectin spatial immunolocalization during in vitro capacitation in Tursiops truncatus spermatozoa

Abstract: Spermatozoa interactions with the female reproductive tract and oocyte are regulated by surface molecules such as glycocalyx. The capacitation process comprises molecular and structural modifications which increase zona pellucida binding affinity. Lectins allowed us to describe glycocalyx changes during maturation, capacitation and acrosome reaction. This study had as its aim to identify lectin binding patterns using four lectins with different carbohydrate affinity in bottlenose dolphin (Tursiops truncatus) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Such subpopulations have been related with sensitivity to cryopreservation, leading in cases to a reduction in sperm head size [ 41 , 50 ] or even correlated with fragmented DNA [ 64 ]. Nevertheless, dolphin sperm subpopulations have only been described in connection with lectin patterns [ 65 ] and kinetic variables [ 16 ]. In the present study, the types of sperm produced by both males had different traits, as observed by the clusterization of the sperm population, suggesting that a given male may produce a mix of different sperm with different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Such subpopulations have been related with sensitivity to cryopreservation, leading in cases to a reduction in sperm head size [ 41 , 50 ] or even correlated with fragmented DNA [ 64 ]. Nevertheless, dolphin sperm subpopulations have only been described in connection with lectin patterns [ 65 ] and kinetic variables [ 16 ]. In the present study, the types of sperm produced by both males had different traits, as observed by the clusterization of the sperm population, suggesting that a given male may produce a mix of different sperm with different functions.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most convenient method for detecting glycoconjugate moieties has been the lectin assay [ 3 , 4 ]. This methodology revealed distinct changes in glycosylated sperm constituents during the capacitation process in mammals [ 5 , 6 , 7 , 8 , 9 ]. Thereby, the removal of sialic acid [ 10 ] or the remarkable mannose or N-acetylgalactosamine redistribution through different membrane domains has been reported during in vitro capacitation [ 5 , 9 ], elucidating the potential role of these conjugates.…”
Section: Introductionmentioning
confidence: 99%